PENGARUH MEDIA FILM LASKAR PELANGI TERHADAP KETERAMPILAN MENULIS PUISI AKROSTIK SISWA KELAS V SD - Bagas Satria Badalu; Rosidah, Cholifah Tur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problems behind this research are students' skills in writing acrostic poetry, lack of use of learning media, lack of teacher attention to students in practicing writing acrostic poetry. The aim of this research was to determine the influence of the Laskar Pelangi film media on the acrostic poetry writing skills of fifth grade elementary school students. This type of research uses quantitative research with a